2008
DOI: 10.1021/ja7109579
|View full text |Cite
|
Sign up to set email alerts
|

The Photo-Favorskii Reaction of p-Hydroxyphenacyl Compounds Is Initiated by Water-Assisted, Adiabatic Extrusion of a Triplet Biradical

Abstract: p-Hydroxyphenacyl is an effective photoremovable protecting group, not least due to the fast release of its substrates, accompanied by a photo-Favorskii rearrangement of compounds 1 to p-hydroxyphenylacetic acid (2) that is transparent down to 300 nm. First used for the release of ATP from 1 (X = ATP) a decade ago, 1 the reaction has been employed in a variety of fields as diverse as neurobiology, 2 enzyme catalysis, 3 and biochemistry. 4 The nature and timing of the bond-making and bond-breaking events have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
151
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(169 citation statements)
references
References 20 publications
16
151
1
1
Order By: Relevance
“…[34] Givens and co-workers also have suggested that a water molecule chain can carry a proton from the acidic p-OH site to the leaving-group phosphate. [35] In the case of KP, the hydrogen atom in the carboxyl group seems too far to be captured by the n-p* excited triplet-state carbonyl group by means of intramolecular hydrogen transfer. However, this process could take place through a bridge of hydrogen bonds among water molecules that connect the carbonyl and carboxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…[34] Givens and co-workers also have suggested that a water molecule chain can carry a proton from the acidic p-OH site to the leaving-group phosphate. [35] In the case of KP, the hydrogen atom in the carboxyl group seems too far to be captured by the n-p* excited triplet-state carbonyl group by means of intramolecular hydrogen transfer. However, this process could take place through a bridge of hydrogen bonds among water molecules that connect the carbonyl and carboxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies revealed the signature absorption profile of this biradical intermediate through the appearance of three transitory bands at 320, 430, and 440 nm with a lifetime of 0.6 ns. 10 The phenoxy-oxyallyl biradical triplet intersystem crosses to the singlet biradical followed by ring closure to form the putative spirodienedione 14 originally suggested by Anderson and Reese 13 for the photo-Favorskii rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…The singlet biradical had no barrier to closure and hence was not predicted to have a significant lifetime, decaying immediately to the spirodienone. 10 The biradicals are believed to be generated through out-of-plane rotation of the acyl group with rotations that range from 8.0 ° for 1 to 41.8 ° for 8. The large twist angle for 8 is intriguing in that it may suggest a potential link between extent of fluoro substitution, particularly at the ortho positions, and the stabilization of the oxyallyl-phenoxy biradical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reakcija se odvija iz tripletnog pobuđenog stanja biradikalskog tipa, gdje nakon dekarbonilacije nastaje QM 74a. 54 Također je studirana reakcija fotogeneriranja QM-a 98 iz 4-hidroksiacetofenona 97 (slika 12).…”
unclassified